FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS WONOREJO SAMARINDA TAHUN 2017 - Novi Anggun Pusvitasary (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2017)
Pneumonia disease is the leading cause of death of babies in the world. The prevalence of pneumonia in infants is 18.5 / mil. Data from Samarinda City Health Office during the last 1 year there are 91 cases of pneumonia in Karang Anyar Village and 63 cases in Teluk Lerong Ulu Village. Factors causing pneumonia are toddler factors, behavioral factors, and environmental factors. The results show there is a relationship between house humidity (p value = 0,013; OR = 0,192), house dwelling density (p value = 0,024; OR = 0,214), and family member smoking behavior (p value = 0,006; OR = 10,450) with incidence of pneumonia in toddlers in the Working Area of Puskesmas Wonorejo Samarinda. There was no correlation between house temperature (p value = 0,214; OR = 0,337), house lighting (p value = 0,095; OR = 3,188) and family disease history (p value = 0,707; OR = 0,753) with Pneumonia occurrence in infant in region Work Puskesmas Wonorejo Samarinda. It was concluded that there was a relationship between house humidity, home dwelling density, and smoking behavior of family members with the incidence of pneumonia in infants. It is recommended to be able to apply housing health requirements that meet health standards to reduce the incidence of pneumonia in infants and change smoking habits.